Anticorrosive coating, preparation method, application and refrigerator
Patent Information
- Application Number
- CN202411110200.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-08-13
AI Technical Summary
[0005]本发明针对现有防腐涂料不能满足冰箱内部金属制件对防止重金属迁移的要求的技术问题,提出一种具有优异的防腐性能以及重金属吸附功能的防腐涂料、制备方法、应用及冰箱,所述防腐涂料为共价有机骨架/功能化羟基磷灰石改性的水性聚氨酯涂料,所用原材料均无毒,满足冰箱内使用要求;本发明防腐涂料为高聚合度涂料,交联密度大,稳定性强,应用于冰箱内部金属制件,能够起到防止重金属从冰箱的金属部件迁移至内部空间,造成食物污染的作用
[0014]本发明还提供了上述防腐涂料的应用,所述防腐涂料涂覆于再生金属表面形成涂层实现防腐和重金属吸附功能。
Smart Images

Figure BDA0004991973610000131 
Figure BDA0004991973610000132 
Figure BDA0004991973610000133
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology, and particularly relates to an anti-corrosion coating, its preparation method, its application, and a refrigerator. Background Technology
[0002] The EU's carbon border adjustment mechanism regulations primarily impact the home appliance industry by driving its transition to low-carbon practices, enhancing market competitiveness, and addressing potential carbon barriers. In the refrigerator industry, many internal components are made of metal. For these components, the use of widely available recycled metals can significantly reduce overall carbon emissions. Furthermore, consumers' desire for green consumption also creates a strong demand for recycled materials.
[0003] However, metal components inside refrigerators that come into direct contact with food pose a risk of heavy metal migration, potentially causing food contamination and impacting consumer health. The high humidity inside refrigerators exacerbates metal corrosion, increasing the risk of heavy metal leaching. Since recycled metals originate from scrap metal recycling, they contain numerous impurities and heavy metals. Using recycled metals in refrigerator components that come into direct contact with food raises concerns about heavy metal migration, inevitably causing consumer anxiety regarding the heavy metal content and migration potential of recycled materials. Furthermore, the high humidity inside refrigerators further restricts the use of recycled metals. In addition, many countries have specific requirements regarding heavy metal migration limits for imported metal materials.
[0004] Currently, coating protection is a common method for metal corrosion prevention. While existing anti-corrosion coatings can prevent moisture and corrosive media from penetrating the metal substrate and improve the metal's corrosion resistance, the high humidity environment inside a refrigerator, used for food preservation, means that existing anti-corrosion coatings cannot meet the requirements for preventing heavy metal migration from the internal metal components. Therefore, providing a heavy metal-absorbing anti-corrosion coating to avoid heavy metal contamination inside refrigerators is a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0005] This invention addresses the technical problem that existing anti-corrosion coatings cannot meet the requirements for preventing heavy metal migration from metal components inside refrigerators. It proposes an anti-corrosion coating with excellent anti-corrosion performance and heavy metal adsorption function, its preparation method, application, and a refrigerator. The anti-corrosion coating is a waterborne polyurethane coating modified with a covalent organic framework / functionalized hydroxyapatite. All raw materials used are non-toxic, meeting the requirements for use inside refrigerators. This invention's anti-corrosion coating is a high-polymerization coating with high crosslinking density and strong stability. When applied to metal components inside refrigerators, it can prevent heavy metals from migrating from the refrigerator's metal parts into the internal space, thus preventing food contamination.
[0006] To achieve the above objectives, the present invention provides an anti-corrosion coating. The technical solution adopted is as follows: an anti-corrosion coating, wherein the raw materials for preparing the anti-corrosion coating include a heavy metal adsorption type anti-corrosion filler, wherein the heavy metal adsorption type anti-corrosion filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of the covalent organic framework to the functionalized hydroxyapatite is 7:(3-5); the preparation process of the covalent organic framework / functionalized hydroxyapatite includes the following steps: S1, preparing functionalized hydroxyapatite containing epoxy groups; S2, loading the functionalized hydroxyapatite onto the covalent organic framework according to a mass ratio of (3-5):7, to obtain the covalent organic framework / functionalized hydroxyapatite. It is understood that, according to actual circumstances, those skilled in the art can adjust the mass ratio of the covalent organic framework and the functionalized hydroxyapatite within the above range; for example, the mass ratio can also be 7:3, 7:4, or 7:5.
[0007] Preferably, step S1 specifically includes the following steps: S1.1, preparing a mixed solution of ethanol and deionized water, adjusting the pH of the mixed solution to 3-4, and then adding KH560 solution dropwise to obtain mixed solution A; S1.2, weighing hydroxyapatite and dissolving it in deionized water, dispersing it evenly by ultrasonication, adding the aqueous solution of hydroxyapatite to mixed solution A, heating in a water bath and stirring magnetically for 2 hours to obtain functionalized hydroxyapatite.
[0008] Preferably, step S2 specifically includes the following steps: S2.1, adding the functionalized hydroxyapatite and the covalent organic framework to an N,N-dimethylformamide solution at a mass ratio of (3-5):7, and dispersing by ultrasonication to obtain a mixed solution B; S2.2, subjecting the mixed solution B to water bath heating and magnetic stirring for a reaction time of 8 hours to obtain a covalent organic framework / functionalized hydroxyapatite.
[0009] Preferably, the covalent organic framework is at least one of TpPa-1, TpPa-2, and TpBD.
[0010] Preferably, the raw materials for preparing the anti-corrosion coating also include water-based polyurethane emulsion, dispersant, thickener, defoamer and leveling agent.
[0011] Preferably, the raw materials for preparing the anti-corrosion coating, by weight, include the following components: 80-100 parts of the waterborne polyurethane emulsion, 50-60 parts of the heavy metal adsorption type anti-corrosion filler, 2-3 parts of the dispersant, 1-3 parts of the thickener, 0.5-1 part of the defoamer, and 0.2-0.8 parts of the leveling agent. It is understood that, based on actual circumstances, those skilled in the art can adjust the weight percentages of each component within the above range. For example, the weight percentages of the waterborne polyurethane emulsion can be 80, 85, 90, 95, 100 parts or any value within the above range; the weight percentages of the heavy metal adsorption type anti-corrosion filler can be 50, 55, 60 parts or any value within the above range; the weight percentages of the dispersant can be 2, 2.5, 3 parts or any value within the above range; the weight percentages of the thickener can be 1, 2, 3 parts or any value within the above range; the weight percentages of the defoamer can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 parts or any value within the above range; and the weight percentages of the leveling agent can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.7, 0.8 parts or any value within the above range.
[0012] Another aspect of the present invention provides a method for preparing the above-mentioned anti-corrosion coating, specifically including the following steps: D1, adding the waterborne polyurethane emulsion, the heavy metal adsorption type anti-corrosion filler, the dispersant, the leveling agent and the defoamer according to the weight parts, and stirring thoroughly; D2, adding the thickener and stirring again to obtain the anti-corrosion coating.
[0013] Preferably, in step D1, the stirring speed is set to 800-1000 rpm and the stirring time is set to 20 min; in step D2, the stirring speed is set to 500-600 rpm and the stirring time is set to 5 min.
[0014] The present invention also provides the application of the above-mentioned anti-corrosion coating, wherein the anti-corrosion coating is applied to the surface of recycled metal to form a coating to achieve anti-corrosion and heavy metal adsorption functions.
[0015] The present invention also provides a refrigerator in which the internal metal components are made from the aforementioned recycled metal coated with an anti-corrosion coating.
[0016] Compared with existing technologies, the advantages and positive effects of this invention are as follows: The anti-corrosion coating of this invention has both anti-corrosion and heavy metal adsorption capabilities, which can prevent recycled metals from directly contacting food, while greatly reducing the risk of heavy metal leaching and eliminating consumers' concerns about the use of recycled metals; The covalent organic framework / functionalized hydroxyapatite modified waterborne polyurethane coating of this invention can effectively prevent heavy metal components from migrating into the refrigerator's internal space. On the one hand, the refrigerator's interior is a high-humidity environment containing many corrosive media. This coating has excellent anti-corrosion capabilities, which can significantly reduce the probability of recycled metals being corroded. On the other hand, it can block food from contacting recycled metal parts, preventing direct contact between the two. Even if corrosive media penetrate the coating and cause corrosion of the recycled metal and leaching of heavy metals, the leached heavy metals will be absorbed by the hydroxyapatite in the coating, thereby passivating and fixing them. Detailed Implementation
[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] This invention provides an anti-corrosion coating, a preparation method, an application, and a refrigerator. The raw materials for preparing the anti-corrosion coating include a heavy metal adsorption type anti-corrosion filler, which is a covalent organic framework / functionalized hydroxyapatite, with a mass ratio of covalent organic framework to functionalized hydroxyapatite of 7:(3-5). The preparation process of the covalent organic framework / functionalized hydroxyapatite includes the following steps: S1, preparing functionalized hydroxyapatite containing epoxy groups; S2, loading the functionalized hydroxyapatite onto the covalent organic framework according to a mass ratio of (3-5):7, to obtain the covalent organic framework / functionalized hydroxyapatite. The waterborne polyurethane coating modified with a covalent organic framework / functionalized hydroxyapatite of this invention can effectively prevent heavy metal components from migrating into the interior space of the refrigerator, significantly reduce the probability of corrosion of recycled metal, and also block food from contacting recycled metal parts. Even if corrosive media penetrate the coating and cause corrosion of recycled metal and leaching of heavy metals, the leached heavy metals will be absorbed by the hydroxyapatite in the coating, thereby passivating and fixing them, thus possessing both anti-corrosion and heavy metal adsorption capabilities.
[0019] The S1 step of this invention for preparing functionalized hydroxyapatite containing epoxy groups specifically includes: S1.1, preparing a mixed solution of ethanol and deionized water, adding acetic acid to adjust the pH of the mixed solution to 3-4, and then adding KH560 solution dropwise to obtain mixed solution A; S1.2, weighing hydroxyapatite and dissolving it in deionized water, dispersing it evenly by ultrasonication, adding the aqueous solution of hydroxyapatite to mixed solution A, heating in a water bath and stirring magnetically for 2 hours to obtain functionalized hydroxyapatite. In the above steps, acetic acid is used as a catalyst. Under acidic conditions, the methoxy group of KH560 first undergoes hydrolysis to generate hydroxyl groups. Hydrolysis is ensured to be complete within 15-20 minutes. After that, hydroxyapatite is added. The hydroxyl groups of KH560 can dehydrate and condense with the hydroxyl groups of hydroxyapatite, thereby functionalizing the hydroxyapatite. At this point, the functionalized hydroxyapatite contains epoxy groups.
[0020] The S2 step of loading the functionalized hydroxyapatite onto a covalent organic framework in this invention specifically includes: S2.1, adding the functionalized hydroxyapatite and the covalent organic framework to an N,N-dimethylformamide solution at a mass ratio of (3-5):7, and dispersing by ultrasonication to obtain a mixed solution B; S2.2, subjecting the mixed solution B to water bath heating and magnetic stirring for 8 hours to obtain a covalent organic framework / functionalized hydroxyapatite. In the above steps, the epoxy groups of the functionalized hydroxyapatite covalently bond with the amino groups of the covalent organic framework, thereby loading the functionalized hydroxyapatite onto the covalent organic framework to obtain a covalent organic framework / functionalized hydroxyapatite.
[0021] In a preferred embodiment, the covalent organic framework is at least one of TpPa-1, TpPa-2, or TpBD, preferably TpPa-1 which has good chemical stability. The covalent organic framework is a typical two-dimensional nanomaterial that can enhance the corrosion resistance of waterborne polyurethane coatings through a physical shielding effect. Since hydroxyapatite is prone to aggregation, which severely reduces its heavy metal ion adsorption capacity, the covalent organic framework of this invention is covalently bonded to hydroxyapatite, improving the dispersibility of hydroxyapatite in waterborne polyurethane coatings. Furthermore, the high specific surface area and abundant amino groups of the covalent organic framework provide more active sites, which is beneficial for the dispersion of hydroxyapatite. In addition, the amino groups of both the covalent organic framework and the waterborne polyurethane readily form coordination bonds with large-radius and easily polarized heavy metal ions, synergistically enhancing the heavy metal adsorption capacity of the coating.
[0022] The anti-corrosion coating provided in this invention also includes other components such as waterborne polyurethane emulsion, dispersant, thickener, defoamer, and leveling agent in its preparation. By weight, it comprises the following raw material components: 80-100 parts waterborne polyurethane emulsion, 50-60 parts heavy metal adsorption type anti-corrosion filler, 2-3 parts dispersant, 1-3 parts thickener, 0.5-1 part defoamer, and 0.2-0.8 parts leveling agent. All raw materials used in this method are non-toxic and meet the requirements for use in refrigerators. The resulting high-polymerization degree coating has a high crosslinking density and strong stability. Hydroxyapatite has ion exchange properties, in which Ca... 2+ It can exchange with heavy metal ions, and phosphate ions combine with heavy metal ions to form phosphate precipitates, thereby adsorbing heavy metal ions in metal parts and passivating them; moreover, hydroxyapatite has a large number of small pores on its surface, with a high specific surface area, which can provide more sites for adsorbing heavy metal ions.
[0023] In a preferred embodiment, the dispersant is selected from at least one of WCA-80, BYK-194N, and HY-4010; the role of the dispersant in this invention is to improve the dispersion performance of the anti-corrosion coating, enhance the fluidity and coating performance of the anti-corrosion coating, thereby strengthening the adhesion and durability of the anti-corrosion coating.
[0024] In a preferred embodiment, the thickener is selected from at least one of HEUR-A, HEUR-B, HEUR-C, HEUR-D, HEUR-01, and HEUR-122; the function of the thickener in this invention is to increase the viscosity and hiding power of the anti-corrosion coating and improve the adhesion of the anti-corrosion coating.
[0025] In a preferred embodiment, the defoamer is selected from at least one of BYK-020, BYK-021, BYK-022, BYK-023, BYK-024, BYK-025, BYK-026, BYK-027, and BYK-028. The function of the defoamer in this invention is to reduce the surface tension of the anti-corrosion coating, reduce the generation of foam, ensure the anti-corrosion effect, and extend the service life of the coating.
[0026] In a preferred embodiment, the leveling agent is selected from at least one of DC-57, BYK333, and TEGO450; the role of the leveling agent in this invention is to improve the leveling and uniformity of the anti-corrosion coating, thereby improving the appearance and quality of the coating.
[0027] The preparation method of the above-mentioned anti-corrosion coating of the present invention specifically includes the following steps: D1, adding waterborne polyurethane emulsion, heavy metal adsorption type anti-corrosion filler, dispersant, leveling agent and defoamer according to the weight parts, and stirring thoroughly at 800-1000 rpm for 20 min; D2, adding thickener, adjusting the speed to 500-600 rpm, and continuing to stir for 5 min to obtain heavy metal adsorption type anti-corrosion coating. In the above steps, covalent organic framework / functionalized hydroxyapatite is added as a filler to the waterborne polyurethane coating, and the above mixture is stirred thoroughly at 800-1000 rpm for 20 min using a coating mixer to improve the dispersibility of the filler; the covalent organic framework / functionalized hydroxyapatite contains amino groups on its surface, and has good compatibility with waterborne polyurethane through the principle of similar dissolves like, and is uniformly dispersed in waterborne polyurethane, so that the obtained anti-corrosion coating has both anti-corrosion and heavy metal adsorption capabilities.
[0028] This invention also provides the application of the anti-corrosion coatings listed in the above technical solutions on the surface of recycled metals.
[0029] The present invention also provides a refrigerator in which the internal metal components are made from the aforementioned recycled metal coated with an anti-corrosion coating.
[0030] To provide a clearer and more detailed description of the anti-corrosion coating, preparation method, application, and refrigerator provided in the embodiments of the present invention, specific embodiments will be described below.
[0031] Example 1
[0032] Raw material composition: by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption type anticorrosive filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. Among them, the heavy metal adsorption type anticorrosive filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0033] The preparation method of the anti-corrosion coating in this embodiment specifically includes the following steps:
[0034] (1) Preparation steps of functionalized hydroxyapatite
[0035] Prepare a 15 mL mixture of ethanol and deionized water at a mass ratio of 1:5; add acetic acid to the mixture to adjust the pH to 3-4, and then add 1 mL of KH560 solution to obtain mixture A.
[0036] Weigh 1g of hydroxyapatite and dissolve it in 10mL of deionized water. Sonicate the solution to disperse it evenly. After 15-20min, add the aqueous solution of hydroxyapatite to mixed solution A. Heat the solution in a water bath at 60℃ and stir magnetically at 350-600rpm for 2h to obtain functionalized hydroxyapatite.
[0037] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0038] The prepared functionalized hydroxyapatite and 1.75 g of covalent organic framework were added to 100 mL of N,N-dimethylformamide solution and sonicated for 20 min to dissolve evenly, resulting in mixed solution B.
[0039] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and stirred magnetically at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of 7:4.
[0040] (3) Preparation steps of coating
[0041] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent, and defoamer to a plastic cup according to the specified weight proportions. Use a paint mixer to thoroughly stir the mixture at 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0042] Example 2
[0043] Raw material composition: by weight, 100 parts of waterborne polyurethane emulsion, 50 parts of heavy metal adsorption type anticorrosive filler, 2 parts of dispersant, 3 parts of thickener, 1 part of defoamer, and 0.8 parts of leveling agent. Among them, the heavy metal adsorption type anticorrosive filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0044] The preparation method of the anti-corrosion coating in this embodiment specifically includes the following steps:
[0045] (1) Preparation steps of functionalized hydroxyapatite
[0046] Prepare a 15 mL mixture of ethanol and deionized water at a mass ratio of 1:5; add acetic acid to the mixture to adjust the pH to 3-4, and then add 1 mL of KH560 solution to obtain mixture A.
[0047] Weigh 1g of hydroxyapatite and dissolve it in 10mL of deionized water. Sonicate the solution to disperse it evenly. After 15-20min, add the aqueous solution of hydroxyapatite to mixed solution A. Heat the solution in a water bath at 60℃ and stir magnetically at 350-600rpm for 2h to obtain functionalized hydroxyapatite.
[0048] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0049] The prepared functionalized hydroxyapatite and 1.75 g of covalent organic framework were added to 100 mL of N,N-dimethylformamide solution and sonicated for 20 min to dissolve evenly, resulting in mixed solution B.
[0050] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and stirred magnetically at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of 7:4.
[0051] (3) Preparation steps of coating
[0052] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent, and defoamer to a plastic cup according to the specified weight proportions. Use a paint mixer to thoroughly stir the mixture at 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0053] Example 3
[0054] Raw material composition: by weight, 80 parts of waterborne polyurethane emulsion, 60 parts of heavy metal adsorption type anticorrosive filler, 3 parts of dispersant, 1 part of thickener, 0.5 parts of defoamer, and 0.2 parts of leveling agent. Among them, the heavy metal adsorption type anticorrosive filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0055] The preparation method of the anti-corrosion coating in this embodiment specifically includes the following steps:
[0056] (1) Preparation steps of functionalized hydroxyapatite
[0057] Prepare a 15 mL mixture of ethanol and deionized water at a mass ratio of 1:5; add acetic acid to the mixture to adjust the pH to 3-4, and then add 1 mL of KH560 solution to obtain mixture A.
[0058] Weigh 1g of hydroxyapatite and dissolve it in 10mL of deionized water. Sonicate the solution to disperse it evenly. After 15-20min, add the aqueous solution of hydroxyapatite to mixed solution A. Heat the solution in a water bath at 60℃ and stir magnetically at 350-600rpm for 2h to obtain functionalized hydroxyapatite.
[0059] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0060] The prepared functionalized hydroxyapatite and 1.75 g of covalent organic framework were added to 100 mL of N,N-dimethylformamide solution and sonicated for 20 min to dissolve evenly, resulting in mixed solution B.
[0061] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and stirred magnetically at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of 7:4.
[0062] (3) Preparation steps of coating
[0063] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent, and defoamer to a plastic cup according to the specified weight proportions. Use a paint mixer to thoroughly stir the mixture at 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0064] Example 4
[0065] Raw material composition: by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption type anticorrosive filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. Among them, the heavy metal adsorption type anticorrosive filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:3.
[0066] The preparation method of the anti-corrosion coating in this embodiment specifically includes the following steps:
[0067] (1) Preparation steps of functionalized hydroxyapatite
[0068] Prepare a 15 mL mixture of ethanol and deionized water at a mass ratio of 1:5; add acetic acid to the mixture to adjust the pH to 3-4, and then add 1 mL of KH560 solution to obtain mixture A.
[0069] Weigh 1g of hydroxyapatite and dissolve it in 10mL of deionized water. Sonicate the solution to disperse it evenly. After 15-20min, add the aqueous solution of hydroxyapatite to mixed solution A. Heat the solution in a water bath at 60℃ and stir magnetically at 350-600rpm for 2h to obtain functionalized hydroxyapatite.
[0070] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0071] The prepared functionalized hydroxyapatite and 2.33 g of covalent organic framework were added to 100 mL of N,N-dimethylformamide solution and sonicated for 20 min to dissolve evenly, resulting in mixed solution B.
[0072] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and stirred magnetically at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of 7:3.
[0073] (3) Preparation steps of coating
[0074] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent, and defoamer to a plastic cup according to the specified weight proportions. Use a paint mixer to thoroughly stir the mixture at 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0075] Example 5
[0076] Raw material composition: by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption type anticorrosive filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. Among them, the heavy metal adsorption type anticorrosive filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:5.
[0077] The preparation method of the anti-corrosion coating in this embodiment specifically includes the following steps:
[0078] (1) Preparation steps of functionalized hydroxyapatite
[0079] Prepare a 15 mL mixture of ethanol and deionized water at a mass ratio of 1:5; add acetic acid to the mixture to adjust the pH to 3-4, and then add 1 mL of KH560 solution to obtain mixture A.
[0080] Weigh 1g of hydroxyapatite and dissolve it in 10mL of deionized water. Sonicate the solution to disperse it evenly. After 15-20min, add the aqueous solution of hydroxyapatite to mixed solution A. Heat the solution in a water bath at 60℃ and stir magnetically at 350-600rpm for 2h to obtain functionalized hydroxyapatite.
[0081] (2) Preparation steps of covalent organic framework / functionalized hydroxyapatite
[0082] The prepared functionalized hydroxyapatite and 1.4 g of covalent organic framework were added to 100 mL of N,N-dimethylformamide solution and sonicated for 20 min to dissolve evenly, resulting in mixed solution B.
[0083] The mixed solution B was transferred to a round-bottom flask, heated in a water bath at 60°C and stirred magnetically at 350-600 rpm for 8 hours, and then centrifuged and dried to obtain a covalent organic framework / functionalized hydroxyapatite with a mass ratio of 7:5.
[0084] (3) Preparation steps of coating
[0085] Add water-based polyurethane emulsion, covalent organic framework / functionalized hydroxyapatite, dispersant, leveling agent, and defoamer to a plastic cup according to the specified weight proportions. Use a paint mixer to thoroughly stir the mixture at 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0086] Comparative Example 1
[0087] Raw material composition: by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption type anticorrosive filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent. The heavy metal adsorption type anticorrosive filler is a mixture of covalent organic framework and functionalized hydroxyapatite, and the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0088] The preparation method of this comparative anti-corrosion coating specifically includes the following steps:
[0089] (1) Preparation steps of functionalized hydroxyapatite
[0090] Prepare a 15 mL mixture of ethanol and deionized water at a mass ratio of 1:5; add acetic acid to the mixture to adjust the pH to 3-4, and then add 1 mL of KH560 solution to obtain mixture A.
[0091] Weigh 1g of hydroxyapatite and dissolve it in 10mL of deionized water. Sonicate the solution to disperse it evenly. After 15-20min, add the aqueous solution of hydroxyapatite to mixed solution A. Heat the solution in a water bath at 60℃ and stir magnetically at 350-600rpm for 2h to obtain functionalized hydroxyapatite.
[0092] (2) Preparation steps of coating
[0093] Add waterborne polyurethane emulsion, a mixture of covalent organic framework and functionalized hydroxyapatite, dispersant, leveling agent and defoamer to a plastic cup according to the weight proportions. Use a paint mixer to stir the mixture thoroughly at 800-1000 rpm for 20 minutes. Then add thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0094] Comparative Example 2
[0095] Raw material composition: by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption type anticorrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent, wherein the heavy metal adsorption type anticorrosion filler is a covalent organic framework.
[0096] The preparation method of this comparative anti-corrosion coating specifically includes the following steps:
[0097] Add water-based polyurethane emulsion, covalent organic framework, dispersant, leveling agent and defoamer to a plastic cup according to the weight proportions. Use a paint mixer to stir the mixture thoroughly at 800-1000 rpm for 20 minutes. Then add thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0098] Comparative Example 3
[0099] Raw material composition: by weight, 90 parts of waterborne polyurethane emulsion, 55 parts of heavy metal adsorption type anti-corrosion filler, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent, wherein the heavy metal adsorption type anti-corrosion filler is hydroxyapatite.
[0100] The preparation method of this comparative anti-corrosion coating specifically includes the following steps:
[0101] Add water-based polyurethane emulsion, hydroxyapatite, dispersant, leveling agent, and defoamer to a plastic cup according to the specified weight proportions. Use a paint mixer to thoroughly stir the mixture at 800-1000 rpm for 20 minutes. Then add a thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0102] Comparative Example 4
[0103] Raw material composition: by weight, 90 parts of waterborne polyurethane emulsion, 2.5 parts of dispersant, 2 parts of thickener, 0.8 parts of defoamer, and 0.5 parts of leveling agent.
[0104] The preparation method of this comparative anti-corrosion coating specifically includes the following steps:
[0105] Add water-based polyurethane emulsion, dispersant, leveling agent and defoamer to a plastic cup according to the weight proportions. Use a paint mixer to stir the mixture thoroughly at 800-1000 rpm for 20 minutes. Then add thickener, adjust the speed of the paint mixer to 500-600 rpm, and continue stirring for 5 minutes to obtain the anti-corrosion coating.
[0106] Performance testing
[0107] The anticorrosion coatings prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to anticorrosion performance tests and heavy metal adsorption performance tests, as detailed below:
[0108] 1. Corrosion resistance test
[0109] The anti-corrosion coatings prepared in Examples 1-5 and Comparative Examples 1-4 were respectively applied to an area of 1*1cm. 2 A working electrode was fabricated on carbon steel. A three-electrode system was obtained using carbon steel with anti-corrosion coating as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet as the counter electrode. The test medium was 3.5 wt.% NaCl solution. The open-circuit potential of the working electrode was measured using the three-electrode system and a CHI-660E electrochemical workstation. The open-circuit potential reached a stable state after the working electrode was immersed for 30 minutes. The data at this point were recorded. Detailed data are shown in Table 1.
[0110] Table 1 Open circuit potentials of Examples 1-5 and Comparative Examples 1-4
[0111]
[0112] 2. Heavy metal adsorption performance test
[0113] 50 mg of potassium chromate was added to 100 mL of deionized water to prepare a Cr(VI) solution. 0.1 mol / L hydrochloric acid was added dropwise to adjust the pH of the solution to 3 (pH=3 is a commonly used value for adsorption experiments). Then, 50 mg of the anti-corrosion coating prepared in Example 1 was added. The mixed solution was fully adsorbed in a shaking chamber at 25 °C at a speed of 180 rpm for 10 hours. The removal rate (R, %) of Cr(VI) was calculated. Detailed data are shown in Table 2.
[0114] Adsorption test solutions for Examples 2-3 and Comparative Examples 1-4 were prepared according to the above steps, and the removal rate (R, %) of Cr(VI) was calculated. Detailed data are shown in Table 2.
[0115]
[0116] In the formula, C0 represents the concentration of Cr(VI) before adsorption, and C e This represents the concentration of Cr(VI) when adsorption reaches equilibrium.
[0117] Table 2. Cr(VI) removal rates of Examples 1-5 and Comparative Examples 1-4
[0118]
[0119]
[0120] Referring to the performance test results in Tables 1 and 2, it can be seen that the open circuit potential of Examples 1-5 is significantly higher than that of Comparative Examples 1-4, indicating that the anti-corrosion coatings of the present invention have stronger corrosion resistance. When the heavy metal adsorption test reaches a stable state, the removal rate of Examples 1-5 is significantly higher than that of the comparative examples, proving that the anti-corrosion coatings of the present invention have the ability to adsorb heavy metals. The addition of covalent organic framework / functionalized hydroxyapatite can effectively enhance the anti-corrosion and heavy metal adsorption functions of waterborne polyurethane coatings. The performance test results of Examples 1-5 show that Example 1 has the highest open-circuit potential and Cr(VI) removal rate, indicating that when the raw materials are formulated according to the ratio of Example 1, the prepared anti-corrosion coating has the best corrosion resistance and heavy metal adsorption performance. This is because the covalent organic framework / functionalized hydroxyapatite is uniformly dispersed in the waterborne polyurethane coating through the mechanism of similar dissolving, which improves the corrosion resistance and heavy metal adsorption performance of the coating. The corrosion resistance and heavy metal adsorption performance of the anti-corrosion coating prepared in Example 3 are lower than those of Examples 1 and 2, indicating that excessive covalent organic framework / functionalized hydroxyapatite is difficult to dissolve in the waterborne polyurethane coating, which leads to a decrease in dispersibility. The open-circuit potential and Cr(VI) removal rate of Examples 4-5 are lower than those of Example 1, which means that when the mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4, the anti-corrosion coating has the best corrosion resistance and heavy metal adsorption performance, that is, the optimal mass ratio of covalent organic framework to functionalized hydroxyapatite is 7:4.
[0121] Compared with Example 1, the heavy metal adsorption type anti-corrosion filler in Comparative Example 1 is a mixture of covalent organic framework and functionalized hydroxyapatite. The corrosion resistance and heavy metal adsorption capacity of Comparative Example 1 are lower than those of Example 1. This is because the covalent organic framework and hydroxyapatite in Comparative Example 1 exist alone. Due to their high specific surface energy, both will undergo varying degrees of agglomeration, which reduces the corrosion resistance and heavy metal adsorption capacity of the anti-corrosion coating.
[0122] Compared with Example 1, the heavy metal adsorption type anti-corrosion filler in Comparative Example 2 is a covalent organic framework. The corrosion resistance and heavy metal adsorption capacity of Comparative Example 2 are both lower than those of Example 1, indicating that the use of excessive covalent organic framework will cause it to agglomerate, resulting in defects at the interface between it and polyurethane, thus reducing the corrosion resistance.
[0123] Compared with Example 1, the heavy metal adsorption type anti-corrosion filler in Comparative Example 3 is hydroxyapatite. The corrosion resistance and heavy metal adsorption capacity of Comparative Example 3 are both lower than those of Example 1, indicating that excessive hydroxyapatite and its own agglomeration phenomenon lead to a decrease in corrosion resistance and heavy metal adsorption capacity. On the one hand, the agglomeration phenomenon leads to interface defects, which can easily become the diffusion path of corrosive media and reduce corrosion resistance. On the other hand, the surface area of agglomerated hydroxyapatite is greatly reduced, which significantly reduces the contact sites with heavy metals and impairs its heavy metal adsorption capacity.
[0124] Comparative Example 4 did not use heavy metal adsorption type anti-corrosion packing. In Comparative Example 2, the heavy metal adsorption type anti-corrosion packing was a covalent organic framework. According to the performance test results, compared with Comparative Example 4, the Cr(VI) removal rate of Comparative Example 2 was increased and the heavy metal adsorption capacity was enhanced. This indicates that the amino groups of the covalent organic framework play a role in adsorbing heavy metals by forming coordination bonds with chromium ions.
[0125] In summary, the anti-corrosion coating of the present invention, by using a covalent organic framework / functionalized hydroxyapatite as a filler, can significantly improve the anti-corrosion and heavy metal adsorption performance of the composite resin, and is suitable for preparing coatings for metal parts inside refrigerators.
[0126] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Any modifications, alterations, evolutions, or improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. An anti-corrosion coating, characterized in that, The raw materials for preparing the anti-corrosion coating include heavy metal adsorption type anti-corrosion fillers and water-based polyurethane emulsion. The heavy metal adsorption type anticorrosion filler is a covalent organic framework / functionalized hydroxyapatite, and the mass ratio of the covalent organic framework to the functionalized hydroxyapatite is 7:(3~5). The covalent organic framework is at least one of TpPa-1, TpPa-2, and TpBD. The covalent organic framework / functionalized hydroxyapatite was prepared by the following steps: S1. Preparation of functionalized hydroxyapatite containing epoxy groups. S2. Load the functionalized hydroxyapatite onto the covalent organic framework according to a mass ratio of (3~5):7 to obtain the covalent organic framework / functionalized hydroxyapatite.
2. The anti-corrosion coating according to claim 1, characterized in that, Step S1 specifically includes the following steps: S1.1 Prepare a mixed solution of ethanol and deionized water, adjust the pH of the mixed solution to 3-4, and then add KH560 solution dropwise to obtain mixed solution A; S1.2 Weigh out hydroxyapatite and dissolve it in deionized water. After ultrasonic dispersion, add the aqueous solution of hydroxyapatite to mixed solution A. Heat in a water bath and stir magnetically for 2 hours to obtain functionalized hydroxyapatite.
3. The anti-corrosion coating according to claim 1, characterized in that, Step S2 specifically includes the following steps: S2.1 The functionalized hydroxyapatite and the covalent organic framework are added to N,N-dimethylformamide solution at a mass ratio of (3~5):7, and the mixture is ultrasonically dispersed to obtain mixed solution B; S2.
2. The mixed solution B is heated in a water bath and magnetically stirred for 8 hours to obtain covalent organic framework / functionalized hydroxyapatite.
4. The anti-corrosion coating according to claim 1, characterized in that, The raw materials for preparing the anti-corrosion coating also include dispersants, thickeners, defoamers, and leveling agents.
5. The anti-corrosion coating according to claim 4, characterized in that, The raw materials for preparing the anti-corrosion coating, by weight, include the following components: 80-100 parts of the waterborne polyurethane emulsion, 50-60 parts of the heavy metal adsorption type anti-corrosion filler, 2-3 parts of the dispersant, 1-3 parts of the thickener, 0.5-1 part of the defoamer, and 0.2-0.8 parts of the leveling agent.
6. The method for preparing the anti-corrosion coating according to claim 5, characterized in that, The preparation method of the anti-corrosion coating specifically includes the following steps: D1. Add the water-based polyurethane emulsion, the heavy metal adsorption type anti-corrosion filler, the dispersant, the leveling agent and the defoamer according to the weight parts, and stir thoroughly; D2. Add thickener and stir again to obtain anti-corrosion coating.
7. The method for preparing the anti-corrosion coating according to claim 6, characterized in that, During the stirring process in step D1, the stirring speed is set to 800-1000 rpm and the stirring time is set to 20 min. During the stirring process in step D2, the stirring speed is set to 500-600 rpm and the stirring time is set to 5 minutes.
8. The application of the anti-corrosion coating according to any one of claims 1-5, characterized in that, The anti-corrosion coating is applied to the surface of recycled metal to form a coating that achieves anti-corrosion and heavy metal adsorption functions.
9. A refrigerator, characterized in that, The metal components inside the refrigerator are made from recycled metal coated with anti-corrosion paint as described in claim 8.
Citation Information
Patent Citations
Hydroxyapatite nanosheet composite anticorrosive paint as well as preparation method and application thereof
CN111978828A
Aqueous coating liquid and functional coating film
JP2007145977A